ANALISIS MIKROFASIES BATUGAMPING DAERAH BATU CERMIN FORMASI BEBULUH, KOTA SAMARINDA, PROVINSI KALIMANTAN TIMUR - Mangalik, Dian; Syam, Muhammad Amin; Puteri, Resty Intan (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2024)
The research area is located in Batu Cermin, Sempaja Utara sub-district, North Samarinda district, Samarinda City, East Kalimantan Province. Batu Cermin is one of the contributors of limestone as a building material for Samarinda and its surrounding areas. Currently, the existence of limestone in the form of outcrops is gradually diminishing due to extensive limestone mining, which necessitates research focused on limestone in this region so that information regarding all aspects of limestone can be documented through the research findings. The main objective of this study is to determine the facies with classifications according to Dunham (1962) and Embry & Klovan (1971), as well as to determine the depositional environment of limestone based on the Standard Microfacies (SMF) according to Flügel (1982), and then to relate it to the Facies Zones according to Wilson (1975).The methods used in this study are descriptive and analytical. The descriptive method is employed to make predictions and derive benefits from a problem that needs to be solved, while the analytical methods used include petrographic analysis, microfacies analysis, and stratigraphic analysis. Field and laboratory observations through descriptions reveal that the Batu Cermin area consists of facies units of mudstone, floatstone, wackestone, grainstone, and sandstone. Referring to the Standard Microfacies (SMF) according to Flügel (1982), it falls under SMF 8 and SMF 11. When linked to Facies Zones (FZ) according to Wilson (1975), the limestone in the research area is deposited in environments of FZ 7 (Open Marine) and FZ 6 (Platform Margin Sand Shoals).